Empowerment Health Cadres In Implementation Of Early Screening Thyroid Disorders In Hulontalangi Village, Gorontalo City - Rista Apriana; Hafni Van Gobel; Fatmawaty Mohammad; Eka Firmansyah Pratama (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Indonesia is the highest in Southeast Asia in thyroid disorders, there are 1.7 million people  (IMS Health survey, 2015). Prevalence of thyroid disease incidence in Gorontalo according to Basic Health Research (Riskesdas, 2013) Gorontalo occupies the 28th position of 33 provinces with a diagnosis of hyperthyroid disease there are 2,264 people with thyroid desease. Data from the health service in 2019 said the highest number in Gorontalo was the working area of Hulontalangi Health Center, which was as many as 50 cases. The number is expected to continue to increase due to the lack of public knowledge about recognizing the symptoms of thyroid disorder. To solves these problems, it is important to do socialization and assistance to health cadres in conducting early detection of thyroid disorders in the community. The purpose of this activity is to increase knowledge and skills for health cadres in conducting early screening of thyroid disorders. The partner village in this activity is Hulontalangi Village of Gorontalo City with the target of the activity is a health cadre of 22 people. The methods carried out in this activity are (1) health education and training of thyroid disorders, (2) early screening training of thyroid disorders (3) advocacy through cadre assistance in early screening of thyroid disorders in the community. The results of this activity showed an increase in cadre knowledge about thyroid disorders, an increase in cadre skills in early detection of thyroid disorders and we found 11 new cases of thyroid disorder. With the results of the new case findings, handling in patients can be done immediately and optimally.